Persepsi Terhadap Iklan Youtube Pada Kalangan Mahasiswa - Roy Poernomo Saputra Oktavia; Nora Nailul Amal (Jurnal Komunikasi Massa, 2024)
This study is entitled PERCEPTION ON YOUTUBE ADVERTISING FROM UNIVERSITY’S STUDENT (Qualitative Study on YouTube Ad’s Value from UNS’ student). This study aims to find out how the perceptions of students on YouTube advertisements are also used as research objects and what attributes appear in the formation of advertising values and their relationship in shaping consumer purchasing intention. This study used descriptive qualitative method. Theories that are considered relevant to this research are New Media, YouTube, Advertising, Perception, University Students. The sampling technique is using Purposive Sampling from university students that are in accordance with the criteria of the researcher in determining prospective informants. Data collecting techniques were carried out by the method of focus group discussion (FGD) and documentation. The validity of the data are tested using triangulation techniques by data and theory. Data analysis techniques used interactive analysis from Miles and Hubberman which included data collecting, data reduction, data presentation, and conclusion drawing. From the research, attributes of pre-roll advertising like the value of humor, moral values, narrative/storytelling, motion graphics, easy-to-remember jingles, and sales promotions are proved to form positive advertising values. However, only sales promotions that explicitly have a direct relationship in shaping consumer purchasing intention. As for negative ad value forming attributes, namely mid-roll ads, monotonous advertisements, badly-edited ads, annoying advertisements, inappropriate advertisements , and ads with bad jingles. All negative attributes can play a role in shaping skipping behavior and anti-advertising behavior.